2012
DOI: 10.1128/jcm.06307-11
|View full text |Cite
|
Sign up to set email alerts
|

A Novel δ-Hemolysis Screening Method for Detecting Heteroresistant Vancomycin-Intermediate Staphylococcus aureus and Vancomycin-Intermediate S. aureus

Abstract: We assessed a new screening method, based on ␦-hemolysin production in the presence of 6 mg/liter vancomycin, to distinguish heteroresistant vancomycin-intermediate Staphylococcus aureus (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…This is in agreement with other reports showing that agr -negativity is commonly selected during the course of infections [8]. Multivariate analysis also revealed that glycopeptide resistance was significantly associated with agr dysfunction ( p  = 0.02; CI 95%: 1.20–12.76) (Table 3), in accordance with previous studies [14][16]. Interestingly, methicillin resistance, which was associated with agr dysfunction in the univariate analysis (Table 2), appeared to be a confounding factor in the logistic regression model (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with other reports showing that agr -negativity is commonly selected during the course of infections [8]. Multivariate analysis also revealed that glycopeptide resistance was significantly associated with agr dysfunction ( p  = 0.02; CI 95%: 1.20–12.76) (Table 3), in accordance with previous studies [14][16]. Interestingly, methicillin resistance, which was associated with agr dysfunction in the univariate analysis (Table 2), appeared to be a confounding factor in the logistic regression model (Table 3).…”
Section: Discussionsupporting
confidence: 92%
“…The latter is a reference strain which produces only β-hemolysin on sheep blood agar plates. A zone of enhanced hemolysis is seen at the junctions where β & δ lysis zones overlap [110]. Original results of a representative experiment demonstrating various hemolysin activities on blood agar plates are presented from our laboratory (Figure 8).…”
Section: Qualitative Methodsmentioning
confidence: 99%
“…Quantitative real time reverse transcription PCR (qRTPCR) is used to measure the transcripts of hla & hld in S. aureus isolates and gyrB is used as a normalizer for hld [110], in case of alpha hemolysin 16S rRNA gene was used as internal or reference control [112].…”
Section: Real Time Pcrmentioning
confidence: 99%
“…MBIC and MBEC experiments were performed using a modified version of the Calgary biofilm device method (Ceri et al, 1999;Cafiso et al, 2010). In brief, 20 ml 10 8 c.f.u.…”
mentioning
confidence: 99%